Managed Globalization 2.0: The European Commission’s Response to Trade Politicization - Garcia-Duran, Patricia (2020)
Several studies have sought to explain the politicization of European Union’s (EU) trade policy during negotiations on the Transatlantic Trade and Investment Partnership (TTIP) and the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA). This article contributes to the literature on the politicization of trade by assessing how politicization is addressed by those tasked with the content and implementation of trade policy, namely the European Commission (hereafter Commission). We identify the origin and definition of managed globalization (MG), and thereafter identify, through a qualitative content analysis of EU Trade Commissioners’ speeches from 2013 to late 2017, how the doctrine re-emerged as the leitmotif of EU trade policy. The Commission’s initial response to civil society organizations’ contestation over TTIP and CETA was to insist on the economic benefits of the agreements. As contestation intensified, we find indirect references to MG, as the Commission focused on clarifying that upholding European values was equally important to market access in EU trade policy. Then, from late 2016 until late 2017, the Commission’s messaging was directed primarily at populist fears of trade and globalization; emphasizing that protectionism was unnecessary, and that globalization could be controlled, culminating in the emergence of explicit references to MG. The article expands on existing research on MG by identifying trade politicization as a factor that prompted a modification and expansion of the MG doctrine and its use, while also discussing some accompanying policy changes.